Clinical importance and surgical management of sentinel lymph nodes in the popliteal fossa of melanoma patients. Issue 9 (September 2019) - Nijhuis, Amanda A.G.; de A.O. Santos Filho, Ivan D.; Uren, Roger F.; Thompson, John F.; Nieweg, Omgo E.
Abstract: Background and purpose: Patients with a primary melanoma below the knee may have lymphatic drainage to a sentinel node (SN) in the popliteal fossa. The purpose of this study was to analyze lymphatic drainage to this site and to describe clinical features and surgical management of SNs in the popliteal fossa. Methods: Patients with a primary melanoma below the knee presenting to Melanoma Institute Australia between 1992 and 2013 were analyzed. Those found to have a popliteal SN were evaluated. Data on imaging, SN biopsy, completion lymph node dissection, morbidity and follow-up were analyzed. Results: Lymphoscintigraphy showed drainage to a popliteal SN in 176 of 3902 cases of melanoma below the knee (4.5%). In 96 of these patients (55%) a popliteal SN biopsy was attempted. The procedure failed to identify the node(s) in seventeen of them (18%). Thirteen of the 79 patients (17%) had a positive popliteal SN and in eight (10%) this was the only positive node. The tumor stage of ten patients (13%) changed as a result of the popliteal node biopsy. A positive popliteal node was associated with an increased risk of recurrence and diminished overall survival. Popliteal SN biopsy did not improve regional control or survival. Conclusion: Melanomas below the knee infrequently drain to lymph nodes in the popliteal fossa. Although popliteal SN biopsy can be challenging, it is worthwhile, providing improved staging and guiding subsequent management.